Evaluation of the quality and quantity of some local and imported honey varieties in the Middle Euphrates governorates - AL-Sirraj, Manal A.; ALI, Riyadh S.; AL-Selawy, Razaq L.; Awad, Haifa A.; Khdem, Ali A.; Mouhsan, Zeina M.; Lateef, Sabreen M. (Journal of Kerbala for Agricultural Sciences, 2018)
The study was conducted to evaluate the quality of samples of different types of local honey produced from different sampling from the Middle Euphrates and imported areas at Karbala University for the period from 1 / 12-1 / 9/2017. The sample included 11 samples. The results showed variation in the percentage of humidity, (16.3% - 19.8%). It was noted that the ash content ranged from 0.2211-0.5433%. The pH values ​​of the honey samples were different, with the highest pH value in model 9 being 3.9, the lowest pH was 2.2 for Fig. 5, and the total pH scores were 22.8 mg kg for Model 9, The results showed a significant difference in the values ​​of efficacy. The results obtained from the sugars estimate showed a difference in total sucrose and glucose, with the highest value of 73.9% for model 11 while the lowest value for total sugars was 64.3% for Fig. 9. For the models given the highest values For the sample 2 was 38.9 mg g and the lowest value of the sample No. 9 was 22.4 mg g. The results of the detection of the enzyme calcoside oxidase showed a clear difference in the effectiveness of the enzyme was 0.99 mmol mol min, 11 was less effective for the enzyme in model 2 amounted to 0.22 mmol mol min. The results of the study within the limits of the Iraqi standard. The results show that the majority of the local models of the Iraqi standard for ash, which are not more than 0.3%, are identical to the sample 11 and 10, which are imported honey samples. The ash is below the limit permitted in the Iraqi standard, The results of the study showed that the total acidity ratio of all samples was consistent with the Iraqi standard. The results of the estimate of total sugars within the limits of the Iraqi specifications and the Constitution of the Food,